(untitled) (Research, Society and Development, 2024)
Wernicke-Korsakoff Syndrome (WKS) is a debilitating neuropsychiatric condition, characterized by a classical triad of symptoms: Wernicke’s encephalopathy, which includes mental confusion, ataxia, and ophthalmoplegia; and Korsakoff’s syndrome, which involves deficits in both anterograde and retrograde memory, confabulation, and mood alterations. This syndrome is commonly associated with chronic alcohol consumption and thiamine deficiency, although it can also occur in cases of malnutrition, gastrointestinal disorders, bariatric surgery, among others. To initiate the review process, a search was conducted in the PubMed electronic database with the aim of identifying studies published in the last 10 years (2014 to 2024) that addressed advances in the diagnosis and treatment of WKS. The specific MESH descriptors used were "Wernicke-Korsakoff Syndrome", "Diagnosis", "Treatment", "Therapeutics". These terms were selected to ensure the inclusion of studies addressing different aspects related to the diagnosis and treatment of WKS, from new diagnostic techniques to emerging therapeutic strategies. After the initial search, the results were filtered to include only studies relevant to the theme of the review. The inclusion criteria required that studies specifically addressed advances in the diagnosis and treatment of Wernicke-Korsakoff Syndrome and provided insights into current and future perspectives in this area. Studies that did not meet these criteria were excluded from the review. The conclusion of this analysis on the treatment of Wernicke-Korsakoff Syndrome highlights the importance of multidisciplinary and evidence-based approaches for the effective management of this complex neuropsychiatric condition. Recent advances in early diagnosis, thiamine therapy, and cognitive rehabilitation represent significant progress in the treatment of WKS, providing improvements in the quality of life of affected patients.